Kinetics of Oxidant of Hexahydroxycyclohexane by Os(VIII) Continuously Regenerated by Hexacyanoferrate(III) ions - Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of hexahydroxycyclohexane (mesoform) by alkaline Os(VIII) which was continuously regenerated by Fe(CN)63- was studied in the 1.0 M-10.0 M [OH- ] and 293 K-313 K temperature range. The rate of the reaction was found to be one each with respect to Os(VIII) and Fe(CN)63-. Suitable mechanism consistent with the observed kinetics has been proposed.